Anti-inflammatory effect of a selective 11β-hydroxysteroid dehydrogenase type 1 inhibitor via the stimulation of heme oxygenase-1 in LPS-activated mice and J774.1 murine macrophages - Sung Bum Park (Journal of Pharmacological Sciences, 2016)
11β-Hydroxysteroid dehydrogenase type 1 (11β-HSD1) converts inactive cortisone to the active cortisol. 11β-HSD1 may be involved in the resolution of inflammation. In the present study, we investigate the anti-inflammatory effects of 2-(3-benzoyl)-4-hydroxy-1,1-dioxo-2H-1,2-benzothiazine-2-yl-1-phenylethanone (KR-66344), a selective 11β-HSD1 inhibitor, in lipopolysaccharide (LPS)-activated C57BL/6J mice and macrophages. LPS increased 11β-HSD1 activity and expression in macrophages, which was inhibited by KR-66344. In addition, KR-66344 increased survival rate in LPS treated C57BL/6J mice. HO-1 mRNA expression level was increased by KR-66344, and this effect was reversed by the HO competitive inhibitor, ZnPP, in macrophages. Moreover, ZnPP reversed the suppression of ROS formation and cell death induced by KR-66344. ZnPP also suppressed animal survival rate in LPS plus KR-66344 treated C57BL/6J mice. In the spleen of LPS-treated mice, KR-66344 prevented cell death via suppression of inflammation, followed by inhibition of ROS, iNOS and COX-2 expression. Furthermore, LPS increased NFκB-p65 and MAPK phosphorylation, and these effects were abolished by pretreatment with KR-66344. Taken together, KR-66344 protects against LPS-induced animal death and spleen injury by inhibition of inflammation via induction of HO-1 and inhibition of 11β-HSD1 activity. Thus, we concluded that the selective 11β-HSD1 inhibitor may provide a novel strategy in the prevention/treatment of inflammatory disorders in patients.